Morpho-Functional Architecture of the Golgi Complex of Neuroendocrine Cells - Martínez-Alonso, Emma; Tomás, Mónica; Martínez-Menárguez, José A. (Frontiers in Endocrinology, 2013)
In neuroendocrine cells, prohormones move from the endoplasmic reticulum to the Golgi complex, where they are sorted and packed into secretory granules. The Golgi complex is considered the central station of the secretory pathway of proteins and lipids en route to their final destination. In most mammalian cells, it is formed by several stacks of cisternae connected by tubules, forming a continuous ribbon. This organelle shows an extraordinary structural and functional complexity, which is exacerbated by the fact that its architecture is cell type-specific and also tuned by the functional status of the cell. It is, indeed, one the most beautiful cellular organelles and, for that reason, perhaps the most extensively photographed by electron microscopists. In recent decades, an exhaustive dissection of the molecular machinery involved in membrane traffic and other Golgi functions has been carried out. Concomitantly, detailed morphological studies have been performed, including 3D analysis by electron tomography, and the precise location of key proteins has been identified by immunoelectron microscopy. Despite all this effort, some basic aspects of Golgi functioning remain unsolved. For instance, the mode of intra-Golgi transport is not known, and two opposing theories (vesicular transport and cisternal maturation models) have polarized the field for many years. Neither of these theories explains all the experimental data so that new theories and combinations thereof have recently been proposed. Moreover, the specific role of the small vesicles and tubules which surround the stacks needs to be clarified. In this review, we summarize our current knowledge of the Golgi architecture in relation with its function and the mechanisms of intra-Golgi transport. Within the same framework, the characteristics of the Golgi complex of neuroendocrine cells are analyzed.